1989
DOI: 10.1071/ar9890791
|View full text |Cite
|
Sign up to set email alerts
|

N2 fixation and its value to soil N increase in lupin, field pea and other legumes in south-eastern Australia

Abstract: N2 fixation and its potential contribution to increasing soil total N were estimated in field-grown crops of lupin and pea in 21 trials at 10 locations in New South Wales and Victoria, during 1984 to 1987. Chickpea, faba bean and annual medic were included at some sites. Across experiments there were differences in annual rainfall (267 to 646 mm), soil N (0.02 to 0.20%), soil pH (CaCl2,4.3 to 8.0) and sowing date (24 April to 16 June). Most experiments were conducted on acidic (pH < 4.8) red-earth, the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(46 citation statements)
references
References 0 publications
3
40
1
2
Order By: Relevance
“…In landscape studies, Androsoff et al (1995) and concluded that N 2 fixation was controlled primarily at the micro-scale level (<3-m and 1.5-m distance, respectively) rather than at the landscape-scale level, with available soil N and water being controlling factors. Because field pea may have a high NHI, which is similar to, or higher than the %Ndfa, the contribution to the N status of soil will usually be small at best, even when stover is not removed (Senaratne and Hardarson 1988;Evans et al 1989;Jensen 1989). A net depletion of soil N will likely occur if the stover is removed.…”
Section: Mots Clésmentioning
confidence: 99%
See 1 more Smart Citation
“…In landscape studies, Androsoff et al (1995) and concluded that N 2 fixation was controlled primarily at the micro-scale level (<3-m and 1.5-m distance, respectively) rather than at the landscape-scale level, with available soil N and water being controlling factors. Because field pea may have a high NHI, which is similar to, or higher than the %Ndfa, the contribution to the N status of soil will usually be small at best, even when stover is not removed (Senaratne and Hardarson 1988;Evans et al 1989;Jensen 1989). A net depletion of soil N will likely occur if the stover is removed.…”
Section: Mots Clésmentioning
confidence: 99%
“…Field pea will have a direct benefit on the soil N status only if the amount of N fixed is greater than the amount of N removed in the seed, i.e., the percentage of plant N derived from the atmosphere (%Ndfa) exceeds the NHI, defined as the proportion of N in the seed relative to total aboveground biomass (seed + stover) N, and provided the stover is not removed from the field. Comparisons of amount of N 2 fixed and seed N harvested, indicate final N balances ranging from -32 to +106 kg N ha -1 for field pea (Evans et al 1989;Maidl et al 1996). Field pea generally fixes about one-half or more of its N requirements (Bremer et al 1988;Cowell et al 1989;Androsoff et al 1995 …”
mentioning
confidence: 99%
“…However, soil nitrogen (N) supplementation by legume production varies with legume crop, soil mineral N content, sowing time and the growth rate of the plant. Plant biomass has been shown to correlate strongly with plant N release to the ecosystem [41,57]. Using the method of Matthews and Marcellos [40] to estimate the levels of N added to the soil by faba bean, the S1, S2 and S3 sowing dates in the present study are likely to have fixed 200, 180 and 90 kg·N·ha −1 , respectively for faba bean.…”
Section: Growth and Yield Of Grain Legumes In Post-rice Soilmentioning
confidence: 99%
“…The calculation of potential N fixation by a crop, based on the total dry matter produced in each sowing dates was used with the reported N fixation rate in Australian conditions for faba bean (at a rate of 120 kg·N·ha −1 ) [40] and field pea (N fixation of 100 kg·N·ha −1 ) [41].…”
Section: Plant and Weed Growth And Phenologymentioning
confidence: 99%
“…This is a critical issue because many countries, both developing and developed, have not fully embraced or taken advantage of BNF potential and are substantially reliant upon fertilizer nitrogen to drive agricultural productivity. Grain legumes fix approximately 20 to 100 kg·N·ha −1 ·yr −1 and use almost the entire amount of fixed nitrogen in grain production [2]. Many USA extension publications tend to credit only 10 to 25 kg·N·ha −1 for previous grain legume crops.…”
Section: Introductionmentioning
confidence: 99%